67.8k views
3 votes
(g(1) = 51
lg(n) = g(n-1) + 2
Find an explicit formula for g(n).
g(n) =

1 Answer

3 votes

9514 1404 393

Answer:

g(n) = 2n +49

Explanation:

The recursive formula tells you this is an arithmetic sequence with first term 51 and common difference 2. The explicit formula for such a sequence is ...

an = a1 +d(n -1) . . . . first term a1, common difference d

Using the sequence values, we have ...

g(n) = 51 +2(n -1)

g(n) = 2n +49 . . . . . simplified

User Mathias Nohall
by
6.3k points